IMPLEMENTASI PROGRAM TUJUAN PEMBANGUNAN BERKELANJUTAN (SUSTAINABLE DEVELOPMENT GOALS) PADA KASUS STUNTING DI INDONESIA - Sindy Yulia Putri (Universitas Potensi Utama, 2021)
In 2018, the quality of Indonesian human resources was ranked 87 out of 157 countries. The good growth of Indonesian human resources, of course, starts from the womb or prenatal period, under five years of age, children, adolescents, to working productive ages. This study chose the topic of stunting, because of the urgency to improve the competitiveness of Indonesian human resources in the regional and international realms. Superior human resources are certainly formed from a long process since childhood. This paper aims to apply the concept of sustainable development goals (SDGs) as a framework adopted by the Government of Indonesia in reducing the prevalence of stunting cases and to provide the latest holistic analysis regarding the implementation of SDGs policies by the Government of Indonesia in reducing the prevalence of stunting cases. This study used qualitative research methods. The result of this research is that collaboration between state and non-state actors is needed to handle stunting cases in Indonesia. Starting from the synergy between ministries / institutions and collaboration with academics, public health scholars, companies, and foreign parties. These results are important as recommendations for each stakeholder in implementing the SDGs concept to reduce the prevalence of stunting cases in Indonesia.